2020
DOI: 10.1101/2020.07.25.221044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct microbial communities along the chronic oil pollution continuum of the Persian Gulf converge with oil spill accidents

Abstract: SummaryPersian Gulf hosting ca. 48% of the world’s oil reserves; has been chronically exposed to natural oil seepage. Oil spill events have been studied over the last decade; however, the influence of chronic oil exposure on the microbial community of the Persian Gulf has remained unknown. We performed genome-resolved comparative analyses of the water and sediment’s prokaryotic community along the Gulf’s pollution continuum (Strait of Hormuz, Asalouyeh and Khark Island). The continuous exposure to trace amount… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…This genome also had six copies of alkB/M and was isolated from a PAH-contaminated site [44]. The high HC degradation potential of other members of this genus has also been reported in the marine ecosystem [45,46]. Rugosibacter aromaticivorans (containing 5, 2 and 2 copies of xylX, ndoB, and tmoA genes, respectively), Pseudoxanthomonas_A spadix_B (with 4, 2 and 2 copies of xylX, todC1 and bphA1 genes, respectively), Thauera sp002354895 (4), Pigmentiphaga sp002188635 (4) are other examples of genomes that have multiple copies of the xylX gene.…”
Section: Yx O Co CC Ia _m Yx O Co Cc Al Es P O Ly An G Ia _p O Ly An ...mentioning
confidence: 69%
See 1 more Smart Citation
“…This genome also had six copies of alkB/M and was isolated from a PAH-contaminated site [44]. The high HC degradation potential of other members of this genus has also been reported in the marine ecosystem [45,46]. Rugosibacter aromaticivorans (containing 5, 2 and 2 copies of xylX, ndoB, and tmoA genes, respectively), Pseudoxanthomonas_A spadix_B (with 4, 2 and 2 copies of xylX, todC1 and bphA1 genes, respectively), Thauera sp002354895 (4), Pigmentiphaga sp002188635 (4) are other examples of genomes that have multiple copies of the xylX gene.…”
Section: Yx O Co CC Ia _m Yx O Co Cc Al Es P O Ly An G Ia _p O Ly An ...mentioning
confidence: 69%
“…On the other hand, the recent reconstruction of three metagenome-assembled Thermoplasmatota genomes (Poseidonia, MGIIa-L2, MGIIb-N1) from oil-exposed marine water samples (not included in the GTDB release89) contained enzymes involved in alkane (alkB) and xylene (xylM) degradation [46]. Hence as these global genome depositories continue to expand, we may have to revise or update our findings.…”
Section: Hc Degradation Across Domain Archaeamentioning
confidence: 94%
“…This genome also had six copies of alkB/M and was isolated from a PAH-contaminated site [28]. The high HC degradation potential of other members of this genus has also been reported in the marine ecosystem [29][30]. Rugosibacter aromaticivorans (containing 5, 2 and 2 copies of xylX, ndoB, and tmoA genes, respectively), Pseudoxanthomonas A spadix B (with 4, 2 and 2 copies of xylX, todC1 and bphA1 genes, respectively), Thauera sp002354895 (4), Pigmentiphaga sp002188635 (4) are other examples of genomes that have multiple copies of the xylX gene.…”
Section: Resultsmentioning
confidence: 99%
“…These analyses suggest that HC degradation ability is present in both kstrategist and r-strategists microorganisms. Earlier studies have shown that r-strategist serves as the principal HC degraders after oil spills and at other point sources of pollution in marine environments [33][34][35][36]. Indeed, most obligate hydrocarbonoclastic bacteria are r-strategists (Proteobacteria domain)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation